Dampak Peningkatan Jumlah Wanita Bekerja Karena Meningkatnya Taraf Pendidikan Terhadap Fenomena Shoushika Di Jepang (2002-2007) - Ratna Handayani; Mayumi Salim (Lingua Cultura, 2011)
Shoushika is a phenomenon facing today's Japanese society. Shoushika become a trend since the increasing female workers delay childbearing which consequently decrease the birth growth in Japan. Due to the decreasing number of future generations, the rate of Japanese economy is hampered and causes restlessness in society about the future. The author felt the need to analyze the underlying problems of women workers that delay having children. Its objective is to find the background of working Japanese females delaying childbearing in relation with the rising level of education, career and salary, referring to the feminism theory developed in Japan.